2010
DOI: 10.3109/13814788.2010.495404
|View full text |Cite
|
Sign up to set email alerts
|

Students' and general practitioners' perceptions of a recently introduced clerkship in general practice. A survey from Austria

Abstract: Background: In autumn 2007, the Medical University of Graz (MUG) upgraded the status of general practice in medical training by integrating a compulsory fi ve-week clerkship in general practice surgeries in the sixth and last year of the curriculum. In cooperation with the Styrian Academy of General Practice (STAFAM), more than 200 general practitioners (GPs) had been accredited to introduce medical students to the specifi c tasks, problems and decision-making process in general practice. Between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Twenty-six studies reported students’ evaluation of the quality of the FM clerkship in several countries such as the USA, 28 38 43–47 the UK, 39 48–51 Germany, 52 53 Austria, 30 54 Israel, 55 56 Slovenia, 40 57 Ireland, 58 Pakistan, 59 Sweden, 34 Saudi Arabia, 36 South Africa 60 and Australia. 61 Nineteen (73%) studies used evaluation questionnaires, 30 34 36 38 39 40 46 47 49 50 52–57 59–61 two interviews 39 51 and three focus groups, 39 56 60 either alone or in combination with questionnaires, while six studies used students’ patient encounter or activity logs. 28 43–45 48 58 The questionnaires used Likert or similar rating scales to assess satisfaction of students and most of them included open-ended questions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-six studies reported students’ evaluation of the quality of the FM clerkship in several countries such as the USA, 28 38 43–47 the UK, 39 48–51 Germany, 52 53 Austria, 30 54 Israel, 55 56 Slovenia, 40 57 Ireland, 58 Pakistan, 59 Sweden, 34 Saudi Arabia, 36 South Africa 60 and Australia. 61 Nineteen (73%) studies used evaluation questionnaires, 30 34 36 38 39 40 46 47 49 50 52–57 59–61 two interviews 39 51 and three focus groups, 39 56 60 either alone or in combination with questionnaires, while six studies used students’ patient encounter or activity logs. 28 43–45 48 58 The questionnaires used Likert or similar rating scales to assess satisfaction of students and most of them included open-ended questions.…”
Section: Resultsmentioning
confidence: 99%
“…Students rated their overall satisfaction with the FM clerkship as very high. 30 34 36 38–40 47 49 52–56 59–61 In different countries with different levels of FM development, students repeatedly reported on the high quality of teaching and the variety of learning experiences during FM clerkships. 28 36 39 43–45 48 50–52 56–59 61 62…”
Section: Resultsmentioning
confidence: 99%
“…36 40 49 50 52 59 Students rated their overall satisfaction with the FM clerkship as very high. 30 61 62 Students were satisfied with the quality of the teaching setting and their relationship with FPs as they were enthusiastic, welcoming and friendly, willing to answer questions and set aside time to discuss with them. 28 The most commonly cited satisfactory aspects of FM clerkships were exposure to a variety of health problems including acute and chronic problems, preventive and continuity visits, 39 36 39 56 57 60 Learning experiences in FM clerkships were reported as complementary and reinforcing to those in ambulatory care internal medicine and paediatrics.…”
Section: Synthesis Of Findings On the Impact Of Fm Clerkshipsmentioning
confidence: 99%
“…61 Nineteen (73%) studies used evaluation questionnaires, 30 39 51 and three focus groups, 39 56 60 either alone or in combination with questionnaires, while six studies used students' patient encounter or activity logs. 28 43-45 48 58 The questionnaires used Likert or similar rating scales to assess satisfaction of students and most of them included open-ended questions.…”
Section: Synthesis Of Findings On the Impact Of Fm Clerkshipsmentioning
confidence: 99%
See 1 more Smart Citation